Feasibility of Filters in Processing Facial Images - T.Sasipraba, A.Deepa (International Journal of Advanced Science and Technology, 2019)
The paper discusses the usage of filters in processing human faces. When natural image is processed, the results are obtained as per the application of algorithm. When comparing the result of natural image and processed image, the result is such that the processed image provides better results. The orientation of the proposed algorithm is to retrieve the age from the given input image. The classification of the age is done with the aid of fractal segmentation based algorithm. When the result obtained is compared with various images of diversified quality, the inference is obtained as different images need different filters for processing and to extract the features from it. In this paper the merits of different filters for processing images of different quality is discussed. In processing the facial images, application of uniform filter for images of different quality does not provide accurate results. So based on the quality of image, the appropriate filter is applied. This provides better results in estimating the age of a person with the help of facial image. Keywords: facial image; filters; image quality; classification; feature extraction